PECULIARITIES OF TAXATION BY LAND TAX AND TAX ON PROPERTY OF PHYSICAL PERSONS: HISTORICAL ASPECT - V. Roshchupkina (Вестник Северо-Кавказского федерального университета)
The article assesses the economic nature of land tax and the tax on property of individuals, studies the evolution of taxation ofreal estate objects and land plots, and gives the tools used by the state in relation to land tax and tax on property of individuals. The coefficients that have been used since 1991 and which are involved in calculating the value ofproperty within a specific subject of the federation (Stavropol Territory) are analyzed. A review of the arbitration practice for these taxes. The objects of taxation by land tax and property tax of individuals in the retrospective and perspective periods are studied in detail.